2018
DOI: 10.1111/apt.14866
|View full text |Cite
|
Sign up to set email alerts
|

A STAT4 variant increases liver fibrosis risk in Caucasian patients with chronic hepatitis B

Abstract: Genetic susceptibility to HBV persistence, hepatic inflammation and fibrosis in Caucasians associates with STAT4 rs7574865 variant. Downstream effects on NK cell function through STAT4 phosphorylation-dependent IFN-γ production likely contribute to these effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 39 publications
3
27
0
Order By: Relevance
“…Whether the above findings can be replicated in Caucasian patients infected with hepatitis B or with the early stages of histologically characterised disease, and the underlying mechanisms for the effect are largely unknown. We demonstrated in a large cohort (n = 830), that STAT4 rs7574865 is associated with liver inflammation and fibrosis . Consistent with other reports, STAT4 rs7574865 regulated STAT4 expression in peripheral blood mononuclear cells (PBMC), natural killer (NK) cells and liver.…”
supporting
confidence: 90%
“…Whether the above findings can be replicated in Caucasian patients infected with hepatitis B or with the early stages of histologically characterised disease, and the underlying mechanisms for the effect are largely unknown. We demonstrated in a large cohort (n = 830), that STAT4 rs7574865 is associated with liver inflammation and fibrosis . Consistent with other reports, STAT4 rs7574865 regulated STAT4 expression in peripheral blood mononuclear cells (PBMC), natural killer (NK) cells and liver.…”
supporting
confidence: 90%
“…In addition, several studies investigating polymorphisms in HCC patients have identified a specific STAT4 polymorphism (rs7574865) which increases the risk of HBV-related HCC in several cohorts, including Chinese, Thai, Korean, Vietnamese and Caucasian. This specific rs7574865 STAT4 variant also showed a corresponding reduction in STAT4 mRNA expression levels [72][73][74][75][76]. However, there are still no conclusive studies detailing the exact role of the variant.…”
Section: The Role Of Other Stats In Hccmentioning
confidence: 94%
“…Stage 3 analysis included replicating SNPs as well as SNPs that have been previously reported to associate with cirrhosis in subpopulations, as described in the introduction (Table ) . As above, we included only SNPs with minor allele count >6 in the European populations of UKBB and MGI, which corresponded to minor allele frequency >0.006.…”
Section: Methodsmentioning
confidence: 99%